The Influence of WhatsApp Social Media on the Dissemination of Learning Information - Vera Wijayanti Sutjipto; Kiki Dwi Arviani; ‪Kinkin Yuliaty Subarsa Putri (Ikatan Sarjana Komunikasi Indonesia, 2022)
Learning information needs to be considered to make learning activities more effective to achieve the goals of learning. One of the frequent obstacles to the reporting of learning activities is limited communication space, which causes communication errors in disseminating learning information. WhatsApp is one of the social media platforms which can be used to learn information. The purpose of this study is to see the effect of WhatsApp on the dissemination of learning information in the Communication Studies Program of the State University of Jakarta. This research uses new media theory and information theory. The method of data collection in this research is a survey with a questionnaire. The population for this study comprised 82 students of the Jakarta State University Communication Study Program class of 2019. The number of samples was calculated using the Slovin formula with a margin of error of 10% to 45 people. The sampling technique used simple random sampling, while the data analysis used statistical analysis. The results of this study indicate that the calculated f value is 36.552 with a significance value of 0.000. Thus. it can be seen that the variable x (the social media WhatsApp) affects the variable y (the dissemination of learning information). Hence, it can be denied that WhatsApp social media affects the dissemination of learning information.